English Acquisition of a Female Syrian Immigrant Student of Islamic Elementary School in Indonesia - Ayatiningsih Ayatiningsih (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2019)
Second Language Acquisition (SLA) is of paramount importance in second or foreign language, in this case English, learning. Thus, it is necessary to figure out how a learner acquires English language in non-English speaking countries. This study was aimed at investigating how a female Syirian student living in Indonesia acquires English as her third language and how she enriches English vocabularies. This research was presented in qualitative approach. The participants were a Syrian female student, Louren Haidar, her parents, her friends and also her english teacher. To collect the data, observation, interview and documentation were conducted. The result of the study showed that Lauren acquired English mostly from classroom activities where her teachers played the biggest role. To enrich vocabularies Laured did some strategies such as Arabic-English translation, writing down the new words, and reading a lot. One of the hardest challenges she faced was pronuncing certain sounds in English such as /p/ and /b/, /v/ vs. /f/, /tʃ/ and /dʒ/ ch + j.